Pelatihan Psikoedukasi Sadar Gizi Berbasis Pangan Lokal sebagai Prevensi Stunting di Desa Jaddih Bangkalan - Hanim, Lailatul Muarofah; Romadlani, M. Masqotul Imam; Alisyrofi, Atik Qurrota A’yunin; Safitri, Ardila; Agnes Madrem, Busstommi R.P.; Tsaniyah, Virza; imamromadlani (Universitas Sunan Drajat Lamongan, Indonesia, 2025)
Bangkalan Regency’s stunting rate in 2023 is the highest stunting case compared to the other regencies in Madura. This community service aims to reduce the number of stunting cases both as a preventive measure and for handling stunting in Bangkalan Regency, particularly in Jaddih Village. Applying the training method, this program seeks to increase knowledge about stunting and also skills in making healthy and nutritious processed foods or Complementary Foods for toddlers (MPASI). The result of this community service is that integrated health service post or Posyandu in Jaddih Village are able to produce several MPASI processed foods such as pudding made from sweet corn and tuna fish tofu porridge. The process of producing MPASI processed is an implementation of the insight, knowledge and skills obtained during this program. The outcome of this activity is a concrete step in attempting to overcome the stunting case in Jaddih Village as one of the stunting loci in Bangkalan Regency.